ANALISIS DAMPAK SOSIAL EKONOMI KEBERADAAN TAMBANG EMAS RAKYAT TERHADAP MASYARAKAT DESA LITO - Nining Sudiyarti; Yayat Fitriani; J Jusparnawati (Jurnal Ekonomi & Bisnis, 2021)
This study aims to analyze the socio-economic impact of the existence of a people's gold mine in Lito Village. This study uses a descriptive method with a qualitative approach. Selection of informants through snowball sampling technique. The number of informants used in the study were 5 people consisting of the village head, the head of the Lito Village BPD, Lito Village community leaders, mining communities and non-mining communities. The data analysis technique uses the method developed by Miles and Hubberman. The results showed that the existence of a gold mine in Lito Village had a positive impact on increasing people's income and had a negative impact on changes in community social behavior and environmental damage, the land changed functions so that the quality of the soil became damaged and prone to collapse (landslides) so that it could affect agricultural land.